PD-L1 (CD274) promoter hypomethylation predicts immunotherapy response in metastatic urothelial carcinoma - Niklas Klümper; Lennert Wüst; Jonas Saal; Damian J. Ralser; Romina Zarbl; Jonas Jarczyk; Johannes Breyer; Danijel Sikic; Bernd Wullich; Christian Bolenz; Florian Roghmann; Michael Hölzel; et al. (OncoImmunology)
PD-L1 status assessed by immunohistochemistry (IHC) has failed to reliably predict outcomes for patients with metastatic urothelial carcinoma (mUC) on immune checkpoint blockade (ICB). PD-L1 promoter methylation is an epigenetic mechanism that has been shown to regulate PD-L1 mRNA expression in various malignancies. The aim of our present study was to evaluate the predictive potential of PD-L1 promoter methylation status (mPD-L1) in ICB-treated mUC compared to conventional IHC-based PD-L1 assessment. We quantified mPD-L1 in formalin-fixed and paraffin-embedded tissue sections using an established quantitative methylation-specific PCR assay (qMSP) in a well-characterized multicenter ICB-treated cohort comprising N = 107 patients with mUC. Additionally, PD-L1 protein expression in tumor tissues was assessed using regulatory approved IHC protocols. The effect of pharmacological hypomethylation by the DNA methyltransferase inhibitor decitabine in combination with interferon-γ stimulation in urothelial carcinoma cell lines was investigated by IHC and FACS. mPD-L1 hypomethylation predicted objective response rate at the first staging on ICB. Patients with tumors categorized as PD-L1 hypomethylated (lower quartile) showed significantly prolonged progression-free (PFS) and overall survival (OS) after ICB initiation. In contrast, PD-L1 protein expression status neither correlated with response nor survival. In multivariable Cox regression analyses, PD-L1 promoter hypermethylation remained an independent predictor of unfavorable PFS and OS. In urothelial carcinoma cell lines, pharmacological demethylation led to an upregulation of membranous PD-L1 expression and an enhanced inducibility of PD-L1 expression by interferon γ. Hypomethylation of the PD-L1 promoter is a promising predictive biomarker for response to ICB in patients with mUC.